2018
DOI: 10.1002/isaf.1431
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid performance evaluation of sustainable service and manufacturing supply chain management: An integrated approach of fuzzy dematel and fuzzy inference system

Abstract: The aim of this paper is to propose a comprehensive framework for simultaneously measuring the performance of sustainable service and manufacturing supply chain management. Application of the proposed approach also results in reduced uncertainty of the performance measurement process caused by qualitative criteria evaluation. The proposed approach consists of two main steps. First, the fuzzy decision-making trial and evaluation laboratory (DEMATEL) method has been used to determine important criteria by avoidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Fuzzy inference system: Dixit et al ( 2019) constructed a fuzzy inference system which was incorporated into a system dynamic model to interact with the main SC structure. Pourjavad and Shahin (2018a) applied the fuzzy inference system to evaluate the GSCM performance of companies with respect to green criteria. Amindoust and Saghafinia (2017) proposed a modular model based on the fuzzy inference system to cope with the subjectivity of opinions of decision-makers.…”
Section: Fuzzy Ai Methods In Scmmentioning
confidence: 99%
“…Fuzzy inference system: Dixit et al ( 2019) constructed a fuzzy inference system which was incorporated into a system dynamic model to interact with the main SC structure. Pourjavad and Shahin (2018a) applied the fuzzy inference system to evaluate the GSCM performance of companies with respect to green criteria. Amindoust and Saghafinia (2017) proposed a modular model based on the fuzzy inference system to cope with the subjectivity of opinions of decision-makers.…”
Section: Fuzzy Ai Methods In Scmmentioning
confidence: 99%
“…The method has been successfully employed for the performance evaluation for environmental social sustainability by Duman et al (2018). DEMATEL as a methodology has also been integrated with other techniques, and hybrid applications are developed in the present body of literature (Gao et al , 2018; Pourjavad and Shahin, 2018; Yadav and Barve, 2018; Ocampo et al , 2018; Gopal et al , 2018; Zhou et al , 2018). For example, DEMATEL approaches for handling criteria interactions and possible integration with other MCDM techniques are reviewed by Golcuk and Baykasoglu (2016).…”
Section: Solution Methodologymentioning
confidence: 99%
“…Ehsan Pourjavad, Arash Shahin (2018) applied fuzzy theory to evaluate the performance of sustainable service and supply chain management of manufacturing industry. The results showed that sustainable manufacturing standards had a greater impact on the performance of sustainable supply chain management than sustainable service standards [70].…”
Section: Service-oriented Manufacturing Supply Chainmentioning
confidence: 97%